HOPE teacher rating scale : involving teachers in equitable identification of gifted and talented students in K-12.: involving teachers in equitable identification of gifted and talented students in K-12. Manual / (2021) - Gentry, Marcia Lynne; Peters, Scott J, 1983-; Pereira, Nielsen; McIntosh, Jason S; Fugate, C. Matthew
No abstract available